Molecular detection tool for prompt, reliable and precise diagnosis of the rice weevil, Sitophilus oryzae (Linnaeus) infestation in wheat - Nagpal, Kanika; Jasrotia, Poonam; Jaglan, Maha Singh; Kashyap, Prem Lal; Maanju, Sunny; Kumar, Sudheer (Frontiers in Plant Science, 2025)
The rice weevil (Sitophilus oryzae L.) is one of the most destructive pests of stored cereal grains, particularly wheat, leading to considerable post-harvest losses and posing serious threats to global food security and international trade. Rapid and accurate identification of infestations is essential for implementing timely pest management strategies and adhering to phytosanitary regulations. In this study, we report the development and validation of a molecular diagnostic assay that is rapid, sensitive, and highly specific for the early detection of S. oryzae in stored wheat grains. Two novel species-specific oligonucleotide primer sets—KNSoCox1F1/KNSoCox1R1 and KNSoCox2F1/KNSoCox2R1—were designed to amplify target regions of the mitochondrial cytochrome oxidase subunits I and II (COI and COII), generating diagnostic fragments of 176 bp and 248 bp, respectively. Conventional PCR demonstrated high specificity, with no cross-reactivity observed in other non-target insects or uninfested wheat samples. Further, sensitivity assessments using quantitative real-time PCR (qPCR) revealed detection thresholds as low as 1 picogram of genomic DNA, which corresponds to a single insect per 10 kg of grains. The assay easily operates in moderately equipped molecular laboratories and offers quick results with streamlined workflows or automation, making it ideally suited for use in quarantine stations, grain storage facilities, and entomological diagnostic laboratories. Its reliability, speed, and cost-efficiency make it a powerful tool for pest surveillance, ecological studies, and enhancing biosecurity protocols.